Analisis Kualitas Sistem Informasi Daily Testing Activity Tracker PT. Telekomunikasi Selular menggunakan Metode Webqual 4.0 dan Importance and Performance Analysis (IPA) - Haris Hasan Mangundap; Satrio Hadi Wijoyo; Intan Sartika Eris Maghfiroh (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Telekomunikasi Selular, also known as Telkomsel, is one of the companies working in the field of government-owned telecommunications technology. To ensure its product quality, Telkomsel has an IT Quality Assurance division to make sure a product meets the specified requirements. This division has the Test Execution team to test new products or services to meet the requirements set by Telkomsel before the products are released to the public. Telkomsel's test execution teams and vendors use an information system called LYTTA (Daily Testing Activity Tracker) to record the activity of all teams and vendors. In LYTTA, there has never been a quality measurement and there are some problems regarding the system's interface and features. This research measures the system's quality using Webqual 4.0 and IPA methods. The Webqual 4.0 method has three dimensions, namely usability, information quality, and service quality, to see the user's perspective in using and interacting with the system. The IPA method is used to map the problems that exist in the system, so the problems that need to be addressed first can be classified. This research was done by distributing questionnaires to 54 LYTTA users from three different companies, namely Telkomsel, Wipro, and Telkom Sigma. This research shows two attributes in the top priority category, namely the system's domain and easefulness. For the low priority, there are two attributes, namely the system's unattractive interface and the lack of competency. The other attributes that are not on the priority list mean it already performs well. The recommendations for improvement are made in accordance with existing guidelines.